Cellular Bioreactivity of Micro- and Nano-Plastic Particles in Oysters - Gaspar, Tamara R.; Chi, Richard J.; Parrow, Matthew W.; Ringwood, Amy H. (Frontiers in Marine Science, 2018)
The global usage of plastics has increased dramatically over the last several decades. Polystyrene (PS) is the fourth most common plastic material produced annually due to its many versatile applications. Consequently, there has been a coinciding increase in PS wastes, much of which makes its way into waterways and oceanic habitats. While plastic debris has been shown to adversely affect many marine species as a result of ingestion and entanglement, less is known about the cellular uptake of small-scale plastic particles (nano and micro) by marine invertebrates. In this study, we investigated the potential for uptake of PS nano and micron-sized beads (50 nm and 3 μm) by the Eastern Oyster, Crassostrea virginica. This research was focused on two key issues: (1) how particle size would affect uptake by hepatopancreas (HP) cells in vitro and (2) the difference in uptake of micron and nano particles in vivo between gill and HP tissues. This research confirmed that oysters can accumulate PS beads in their tissues, especially HP tissues. Furthermore, using fluorescent deconvolution microscopy, it was observed that plastic nanoparticles exhibited a much greater propensity for intracellular accumulation in HP cells, primarily into lysosomes via endosomal pathways, indicating the potential for significant bioreactivity and sublethal impacts. While exposures of whole oysters or isolated HP cells to bare PS beads did not cause any significant toxicity (acute or sublethal), nanoplastics are more likely to accumulate intracellularly and to deliver adsorbed toxins directly into cells.